A Novel Approach for Facial Attendance:AttendXNet - Arora, Kawal; Bist, Ankur Singh; Prakash, Roshan; Chaurasia, Saksham (Aptisi Transactions On Technopreneurship (ATT), 2020)
Recent advancements in the area of facial recognition and verification introduced the possibility of facial attendance for various use cases. In this paper we present a system named as AttendXNet. Our method uses the ResNet and Multi-layer feed forward network to achieve the state of art results. Extensive analysis of various deep learning and machine learning techniques is described. Face anti-spoofing is a major challenge in facial attendance. Extended-MobileNet is used to resolve the same issue. We also introduced the end to end pipeline to implement an attendance system for various use cases.